Understanding the effect of competition during evolutionary radiations: an integrated model of phenotypic and species diversification. (10th September 2019) - Aristide, Leandro; Morlon, Hélène
Abstract: Competition can drive macroevolutionary change, for example during adaptive radiations. However, we still lack a clear understanding of how it shapes diversification processes and patterns. To better understand the macroevolutionary consequences of competition, as well as the signal left on phylogenetic data, we developed a model linking trait evolution and species diversification in an ecological context. We find four main results: first, competition spurs trait diversity but not necessarily species richness; second, competition produces slowdowns in species diversification even in the absence of explicit ecological limits, but not in phenotypic diversification even in the presence of such limits; third, early burst patterns do not provide a reliable way of testing for adaptive radiations; and fourth, looking for phylogenetic signal in trait data and support for phenotypic models incorporating competition is a better alternative. Our results clarify the macroevolutionary consequences of competition and could help design more powerful tests of adaptive radiations in nature. Abstract : Competition can drive macroevolutionary change. However, we still lack a clear understanding of how it shapes diversification processes and patterns. To clarify the macroevolutionary consequences of competition we developed and simulated a model linking trait evolution and species diversification in an ecological context. Our results clarify the macroevolutionary consequences of competition and the signal left in comparative data, and could help design more powerful tests of adaptive radiations in nature.